Congenital cytomegalovirus - current state of knowledge on the treatment and prevention of fetuses and newborns - Grego, Katarzyna; Grego, Mateusz; Stojak, Łukasz; Popiela, Dariusz; Urbańska, Karina; Kwiatkowski, Filip; Baczewski, Mateusz; Czyż, Witold (Quality in Sport, 2025)
Cytomegalovirus (CMV) is common pathogen in the human population and one of the most causes of intrauterine infections of the fetus. It is a component of the acronym TORCH describing pathogens which are a significant risk factor for miscarrings or serious damage to the fetus. Symptomatic congenital cytomegalovirus occurs in about 10% of infected newborns and, among of the other things, can cause hearing loosing, vision impairment or cognitive impairment in the children. Importantly, a child who is asymptomatic at the time of delivery is still at risk of developing dysfunctions in the future. Currently there is no effective vaccine against cytomegalovirus. There are attempts to treat pregnant women with antiviral drugs and hyperimmunoglobulins. The treatment is intended to protect the fetus from vertical transmission of the virus or to reduce the effects of infection. An important aspect is the time of starting treatment for the woman and the seroprevalence of expectant mothers. The risk of fetal infection increases with the age of pregnancy. Primary infection of the mother poses a greater danger to the fetus than secondary infection. The key moment of treatment apear to be the first trimester of pregnancy, because it is during this period that the greatest devastation occurs in the rapidly developing fetus. For this reason, the greatest benefit from treatment may be obtained by pregnant women with primary CMV infection in the first trimester of pregnancy. In this article, we will present the problem of congenital cytomegalovirus and describe the current proposals for treatment and prophylaxis used in fetuses and newborns infected with cytomegalovirus, we will present the current state of knowledge about potential side effects of its use.